Resolusi Konflik Internal di SD Muhammadiyah Weleri Tahun 2020: Penelitian - Rijal Wakhid Rizkillah; Budi Setyono; Sriyono Sriyono; Ali Imron; Moch.Fachrizal Alif (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the internal conflict that occurred at Muhammadiyah Weleri Elementary School, involving the principal and teachers. The conflict arose primarily due to perceived unilateral leadership policies, lack of communication, and teacher dissatisfaction with welfare and workload. This study employed a descriptive qualitative approach with interview, observation, and documentation techniques. The conflict analysis was conducted using social conflict theory and conflict analysis instruments such as conflict mapping, the Attitude-Behavior-Context (DSS) triangle, and the onion analysis. The results indicate that internal conflict can be managed through a conflict resolution mechanism based on deliberation, negotiation, and compromise, involving the Muhammadiyah Elementary and Secondary Education Council as a mediator. This research is expected to contribute to conflict management in Muhammadiyah educational institutions.